Water in mineral processing : proceedings of the first international international symposium - Drelich, J.; Hwang, Jiann-Yang (Society for Mining, Metallurgy, and Exploration, 2012)
One of the major challenges confronting the mining and minerals processing industry in the 21st century will be managing in an environment of ever decreasing water resources. Because most mineral processing requires high water use, there will be even more urgency to develop and employ sustainable technologies that will reduce consumption and the discharge of process-affected water. Water in Mineral Processing provides a comprehensive, state-of-the-art examination of this vital issue. A compilation of papers presented at the First International Symposium on Water in Mineral Process.
"The SME Mineral and Metallurgical Processing Division organized this First International Symposium on Water in Mineral Processing during the 2012 SME Annual Meeting in Seattle, Washington."--Page vii.
Keywords: Dredging spoil -- Environmental aspects.; Mineral industries -- Waste disposal -- Environmental aspects.; Mineral industries -- Water-supply.; Water reuse.; elektronické knihy; electronic books